Proceedings of 5th International Conference on Mechanical, System and Control Engineering ICMSC 2021 - Lei, Xuelin; Koryanov, Vsevolod V.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book comprises the proceedings of the 5th International Conference on Mechanical, System, and Control Engineering 2021. The contents of this volume focus on recent technological advances in the field of system dynamics and simulation, precision mechanics, production technology, structural dynamics, nanomaterial engineering, cloud computing and services, energy engineering and management, etc. This book proves a valuable resource for those in academia and industry.
Effect of Fibre Treatment on Tensile Properties in Bamboo Fibre Extraction: A Review Paper -- Spray Solution Combustion Synthesis of NiCu Hollow Spheres -- Approach to the Selection of Classification Features for Integrated and Combined Technological Processes of Metal Ware Manufacturing -- Synthesis and Characterization of PSf-CQD Nanocomposite Membrane via Non-solvent Induced Phase Separation Technique -- Study of the Movement of the Descent Vehicle with an Inflatable Device Made of a Special Material Taking into Account the Arising Asymmetry -- Electrode Shape Design and Current Density Distribution for Stable Plasma Beam Incinerator -- Influence of Materials and their Constitutive Laws on the Stress Fields Produced in the Residual Limb of a Transfemoral Amputation -- Study of the Elastic Field of a Plane Strain Orthotropic Composite Plate Subjected to Uniform Tension -- Comparison of Papaya Cushioning Materials by Ellipsoid Evaluation Method -- Development of Polyamide-Polysulfone Thin Film Composites with Copper-treated Zeolites as Additives for Enhanced Hydrophilicity.
Keywords: Mechanical engineering; Production engineering; Industrial engineering; Mechanical Engineering; Process Engineering; Industrial and Production Engineering; Control theory -- Congresses; Mechanical engineering -- Congresses; Systems engineering -- Congresses